Proteomics and Metabolomics Unveil Codonopsis pilosula (Franch.) Nannf. Ameliorates Gastric Precancerous Lesions via Regulating Energy Metabolism - He, Rupu; Ma, Ruyun; Jin, Zheng; Zhu, Yanning; Yang, Fude; Hu, Fangdi; Dai, Jianye (Frontiers in Pharmacology, 2022)
Objective：This work aimed to systematically evaluate the efficacy of Codonopsis Radix and reveal the mechanism of its effects on suppressing Gastric Precancerous Lesions. Methods: Firstly, we established the Gastric Precancerous Lesions rat model which was induced by N-methyl-N'-nitro-N-nitrosoguanidine, disordered diet and 40% ethanol. The Codonopsis Radix’s anti-Gastric Precancerous Lesions effect was comprehensively evaluated by body weight, pathological section and serum biochemical indexes. Then, quantitative proteomics and metabolomics were conducted to unveil the disturbed protein-network and pharmacodynamic mechanism. Furthermore, serum pharmacology was employed to confirm that Codonopsis Radix’s anti-gastritis and anti-cancer phenotype in cell models. Results: In animal models, Codonopsis Radix had been shown to control inflammation and ameliorate Gastric Precancerous Lesions. Considering the combination of proteomics and metabolomics, we found that Codonopsis Radix could significantly reverse the biological pathways related to energy metabolism which were disturbed by Gastric Precancerous Lesions model. Furthermore, the results of serum pharmacology indicated that the Codonopsis Radix contained serum could ameliorate gastritis injury, and selectively inhibit the proliferation of gastric cancer cells rather than normal cells, which was closely related to ATP production in above cells. Conclusion: In summary, Codonopsis Radix exerted anti-Gastric Precancerous Lesions ability by ameliorating gastritis injury and selectively inhibiting the proliferation of gastric cancer cells rather than normal cells. Proteomics and metabolomics unveiled its efficacy was close related to its regulation of energy-metabolism pathway. This research not only provided new ideas for exploring the mechanism of complex systems such as Chinese herbals, but also benefited the treatment strategy of Gastric Precancerous Lesions via regulating energy metabolism.